(untitled) (Law and Safety, 2018)
The results of the study of hard core criminals’ personality of lucrative and violent types have been presented. The instrument included the methods for studying the accentuations of a character, manifestations of aggressiveness, value orientations, peculiarities of self-regulation of behavior, communication inhibition, emotional intelligence, and strategies to overcome stress situations by hard core criminals, who serve sentences in the form of deprivation of liberty. Using factor analysis, the author has established statistical relationships between variables that were the object of study in this research. Four factors have been identified both in the group of violent and in the group of lucrative criminals. The determined factors in the group of lucrative type cover a total of 78.11 % of dispersion, in the group of violent criminals – 74.08 %. The first three have been found out in both groups of convicts: the first factor “Complex of aggressive behavior” causes the specificity of manifestations of aggressiveness. The second factor “Communication” determines the specifics of communicative interaction. The third factor “Characteristic features” combines the accented features of the character and properties, which correspond to the nature of its peculiarity. At the same time, the content of these factors distinguished for lucrative and violent criminals has been found out. The fourth factor “Subjective control”, found in the lucrative type of convicts, distinguishes characteristics that indicate contradictions in the structure of control localization. Recognition of guilt is faced with an unwillingness to overcome difficulties and be responsible for their actions. This coincides with the data contained in the scientific literature, which testify that lucrative criminals are inherent to recognize their guilt, while justifying this as insuperable external circumstances. The fourth factor of violent type convicts “Values” includes humanistic values that are understood by these subjects without reference to other components of the individual, that is, the values of the higher order are separated from other psychological characteristics. By the results of the factor analysis, the author has differentiated psychological features of lucrative and violent hard core criminals that allows to emphasize the need for a specification of psycho-corrective work with convicted persons of a specified criminal orientation.